Integrating Philosophy in Modern Management for Excellence and Productivity: Cases and Reflections (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The present paper is a part of ongoing research  of the authors in integrating Philosophy into  managerial practices for creating virtuous  employee engagement and organizational  excellence. With the changing scenario  and typical work styles, philosophy has a  significant role in creating positive leadership  who practices compassion, love, and truth  for creating inclusive organizations. In  this paper, the authors have aimed to give  a background of the relevance of Quakers  philosophy to managerial practices by citing  examples through the specific case of Cadbury  Schweppes and other brief reflections across  the globe. The current article claims a great  deal to be learned about business practices by  reflecting on how the Friends, mostly forgotten  and disregarded in the foundation narratives of  management studies, were structured and how  they successfully managed their businesses. The  authors also consider multiple implications  that management studies may derive from  researching the Quakers’ management style  in the future. Consequently, the authors  suggest that now would be the wise moment  to reclaim truthfulness and behave ethically  and constructively.
Keywords: Quakers Philosophy; Management Practice; Cadbury; Community Service; Friends; Social Capital